Existence of solutions for degenerate parabolic equations with singular terms. (January 2016) - Dall'Aglio, Andrea; Orsina, Luigi; Petitta, Francesco
Abstract: In this paper we deal with parabolic problems whose simplest model is { u ′ − Δ p u + B | ∇ u | p u = 0 in  ( 0, T ) × Ω, u ( 0, x ) = u 0 ( x ) in  Ω, u ( t, x ) = 0 on  ( 0, T ) × ∂ Ω, where T > 0, N ≥ 2, p > 1, B > 0, and u 0 is a positive function in L ∞ ( Ω ) bounded away from zero.